Contextualizing toxic elements in the diet: a case for integration of toxic element data into food databases - Jones, Rachel R.; Odenkirk, Melanie T.; Bertoldo, Jackie; Prenni, Jessica E. (Frontiers in Nutrition, 2024)
Food composition data plays a key role in the practice of nutrition. However, nutrition professionals may currently lack the resources they need to integrate information about toxic elements – such as arsenic, cadmium, and lead – in food into the advice they give consumers. Geographic, sociocultural, and individual factors may impact not only the toxic element content of food, but also how the balance between potentially toxic and health-promoting components of food must be weighed. Better integration and contextualization of toxic element data into key food databases could allow for more nuanced, comprehensive nutrition guidance.